The Impact of Quizizz-Based Gamification on Academic Achievement: A Meta-Analysis Across Educational Contexts - Deby Cinthia; M. Giatman; Nurhasan Syah; Nizwardi Jalinus; Krismadinata Krismadinata; Ambiyar Ambiyar (AL-ISHLAH: Jurnal Pendidikan, 2025)
This meta-analysis investigates the overall impact of Quizizz-based gamification on students’ academic achievement across diverse educational contexts, from elementary to higher education. A systematic search of academic databases (Google Scholar, ERIC, Scopus, and institutional repositories) identified 1,340 studies, of which 28 met inclusion criteria. Effect sizes and standard errors from 25 quantitative studies were synthesized using JASP software under a fixed-effects model. The results reveal a large and statistically significant overall effect (Cohen’s d = 0.86, p .001), indicating that Quizizz substantially improves academic performance. Heterogeneity was moderate (I² = 48.6%), and funnel plot analysis with Egger’s test indicated minimal publication bias. Subgroup analysis showed consistent effectiveness of Quizizz across subject areas (e.g., mathematics, science, language learning) and instructional settings (face-to-face, blended, and online learning). These findings suggest that Quizizz is a versatile and pedagogically valuable tool for enhancing student engagement, motivation, and achievement. The study supports the broader adoption of gamified digital tools in modern classrooms and recommends further research to explore long-term effects and contextual moderators.